2019
DOI: 10.3390/ijerph16234793
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Targeted Video Improves Psychosocial Outcomes in Latina Women at Risk of Hereditary Breast and Ovarian Cancer

Abstract: Latina women at risk of hereditary breast and ovarian cancer (HBOC) have lower awareness, knowledge, and use of genetic counseling and testing services (GCT) than non-Latina Whites. Few interventions have been developed to reduce these disparities among at-risk Latinas. This pilot study assessed the impact of a culturally targeted narrative video developed by our team. The study included 40 Latina immigrants living in the United States who were at risk of HBOC, including affected and unaffected women. We asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…One such delivery model is storytelling, which can be employed as a culturally tailored educational intervention method. Several studies have demonstrated the utility of video storytelling in Hispanic/Latinx communities (Baezconde‐Garbanati et al, 2014; Hurtado‐de‐Mendoza et al, 2019, 2020; Murphy et al, 2015). Determining the effectiveness of the method and delivery models of a storytelling intervention may aid researchers and healthcare providers in improved communication and health outcomes for their Spanish‐speaking patients.…”
Section: Introductionmentioning
confidence: 99%
“…One such delivery model is storytelling, which can be employed as a culturally tailored educational intervention method. Several studies have demonstrated the utility of video storytelling in Hispanic/Latinx communities (Baezconde‐Garbanati et al, 2014; Hurtado‐de‐Mendoza et al, 2019, 2020; Murphy et al, 2015). Determining the effectiveness of the method and delivery models of a storytelling intervention may aid researchers and healthcare providers in improved communication and health outcomes for their Spanish‐speaking patients.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have explored the use of narrative educational tools for at-risk Latinas to improve psychosocial outcomes [19,20]. The vast majority of literature on genetic counseling interventions in diverse populations has focused mainly on cancer genetics [21], and there is a dearth of literature on barriers to communication in racially and ethnically diverse pediatric patient populations and their families.…”
Section: Introductionmentioning
confidence: 99%
“…A single‐arm pilot test of the video was conducted with at‐risk Latinas in the United States. The results showed that the video improved cognitive and affective psychosocial outcomes, including attitudes and anticipatory emotions (Hurtado‐de‐Mendoza, Graves, Gómez‐Trillos, Carrera, et al, 2019; Hurtado‐de‐Mendoza, Graves, Gómez‐Trillos, Song, et al, 2020). The present research evaluates whether mindset (abstract or concrete) influences the positive psychosocial outcomes observed in Latinas after they watched a persuasive narrative message in the form of a culturally targeted video (Hurtado‐de‐Mendoza, Graves, Gómez‐Trillos, Song, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%